1998
DOI: 10.2466/pms.1998.86.2.723
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Exercise Motivation and Body-Image Satisfaction among College Students

Abstract: The current study was an expansion of one by Cash, Novy, and Grant in 1994, in which responses of 101 female nursing students were examined for associations between reasons for exercise, frequency of exercise, and body-image satisfaction. In the current study, 78 male and 100 female undergraduates between the ages of 18 and 25 years (M = 21.2, SD = 1.9) from various majors completed a demographics/frequency of exercise survey, two body-assessment inventories, and the Reasons for Exercise Inventory of Silberste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 13 publications
2
28
1
4
Order By: Relevance
“…Japanese students cared more about ideal BMI and followed the dietary regimen more frequently, compared to Korean female students (9). The evaluation of students' dietary habits by sex in the US showed that females cared more about their body weight and used physical exercise for body mass correction more frequently (10).…”
Section: Discussionmentioning
confidence: 99%
“…Japanese students cared more about ideal BMI and followed the dietary regimen more frequently, compared to Korean female students (9). The evaluation of students' dietary habits by sex in the US showed that females cared more about their body weight and used physical exercise for body mass correction more frequently (10).…”
Section: Discussionmentioning
confidence: 99%
“…Research has proven that levels of satisfaction towards body image are associated with regular exercise (Cash, Novy, & Grant, 1994;Smith, Handley, & Eldredge, 1998). The taking up of aerobic dance among adult females has been found to be associated with their self-perceived lack of physical attraction, and those who exercise more frequently have been found to be less satisfied with their own physical stature.…”
Section: Body Imagementioning
confidence: 97%
“…Cash et al 1994;Ingledew and Sullivan 2002;McDonald andThompson 1992, Silberstein et al 1988;Smith et al 1998;Strelan et al 2003;Tiggemann and Williamson 2000). It seems that female sport participants in general often have weight-related motives for their sport participation that are accompanied by body dissatisfaction, weight control, and lower self-esteem.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, so called body-related exercising for weight loss, body tone, or attractiveness has been shown to be related to disturbed eating, body dissatisfaction, and lower self-esteem (Cash et al 1994;McDonald andThompson 1992, Silberstein et al 1988;Smith et al 1998;Strelan et al 2003;Tiggemann and Williamson 2000). Hubbard et al (1998) concluded that female exercisers who exercise particularly for burning calories or losing weight indicated the greatest disturbance on these areas.…”
Section: Introductionmentioning
confidence: 99%